2005
DOI: 10.1111/j.1439-0523.2005.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a molecular CAPS marker for the self-incompatibility locus in Brassica napus and identification of different S alleles

Abstract: Using primers annealing to S locus sequences the cleaved amplified polymorphic sequences (CAPS) method was applied to develop a marker and to characterize different alleles at the self-incompatibility locus in Brassica napus. A segregating F 2 population from a cross of a self-incompatible (SI) and a self-compatible parent, as well as seven SI lines representing four different S alleles were used. Several primers specific to the S locus in B. oleracea and B. campestris, chosen from the literature, allow polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…SI can be introduced into B. napus either by introgression from B. oleracea and B. rapa (MacKay 1977;Goring et al 1992) or by the resynthesis of B. napus from B. oleracea and B. rapa (Gowers 1989;Rahman 2005). The inheritance of SI in B. napus generated by introgression is controlled by a single dominant gene (Goring et al 1992), a single recessive gene (Möring et al 2005), or two genes (Yang et al 2001), while resynthesized B. napus shows a strong dominant SI phenotype (Rahman 2005;Ekuere et al 2004). In natural SC B. napus, self-compatibility is caused by independent mutations in the dominant S haplotype (Okamoto et al 2007); a latent S allele was identified and a suppressor system not linked to the S loci was deduced to mask the S phenotype (Ekuere et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…SI can be introduced into B. napus either by introgression from B. oleracea and B. rapa (MacKay 1977;Goring et al 1992) or by the resynthesis of B. napus from B. oleracea and B. rapa (Gowers 1989;Rahman 2005). The inheritance of SI in B. napus generated by introgression is controlled by a single dominant gene (Goring et al 1992), a single recessive gene (Möring et al 2005), or two genes (Yang et al 2001), while resynthesized B. napus shows a strong dominant SI phenotype (Rahman 2005;Ekuere et al 2004). In natural SC B. napus, self-compatibility is caused by independent mutations in the dominant S haplotype (Okamoto et al 2007); a latent S allele was identified and a suppressor system not linked to the S loci was deduced to mask the S phenotype (Ekuere et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The evidence collected in this study shows that SNP identification represents the best strategy for finding polymorphic markers for the construction of a C. arabica genetic map. CAPS markers have been applied as molecular tools in Arabidopsis (Konieczny and Ausubel 1993), Brassica napus (Möhring et al 2005), and Capsicum annuum L. (Minamiyama et al 2005). These studies report the efficient use of the CAPS method in plants to detect a clear and reproducible polymorphism, easily identified by using enzymes of frequent digestion.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies reported that SI was under the control of a single S locus (Möhring et al 2005;Rahman 2005;Tang et al 2009;Zhang et al 2008a), while some studies suggested suppressor locus control of SI via an unknown mechanism (Ekuere et al 2004;Ma et al 2009;Yang et al 2001 …”
Section: Genetic Analysis Of Si In B Napusmentioning
confidence: 98%
“…Specific markers linked to SI in B. napus lines have been developed to identify different S alleles (Möhring et al 2005). SCAR (sequence-characterized amplified region) markers were developed from S-locus genes and co-segregated with SI lines and self-compatible lines, and its use in marker-assisted selection for the SI phenotype was effective Zhang et al 2008a), which is helpful for improving the maintainer line and accelerating the breeding of SI hybrids in B. napus.…”
Section: Potential Of Si In B Napus Breedingmentioning
confidence: 99%